Peningkatan Hasil Belajar Bercakap Cakap dalam Bahasa Inggris menggunakan Media Puzzle pada Siswa Kelas V SD YPPGI Nokapaka - Satunggale Kurniawan; Rahman, Muhammad Afifi; Mendiron Yigibalom (PT Pustaka Cendekia Group, 2024)
The success of the teaching and learning process is largely determined by a teacher who transfers knowledge through the learning process, in this case learning strategies are important in the learning process. Many lessons in class are carried out by teachers, lessons that are often used in the learning process include: lecture learning, question and answer learning, discussion learning, assignment learning, demonstration learning, field trip learning, group work (inquiry), learning role playing, dialogue learning, argumentative learning, and story telling. Based on the considerations above, it is necessary to develop a learning method that is able to involve student participation as a whole so that teaching and learning activities are not only dominated by certain students. In addition, through choosing this learning method, it is hoped that the source of information that students receive will not only come from the teacher but can also increase student participation and activeness in studying and reviewing existing knowledge, especially English subjects. Based on the background of the problem above, the title of this classroom action research was formulated as follows: